Modelo multicritério para construção do perfil da vaga e apoiar a seleção de candidatos na divisão logística integrada frimesa - Zamin, Simone (2024)
During the recruitment and selection process, those responsible for vacancies face the challenge of dealing with a diversity of variables and a multitude of criteria associated with skills and abilities on a daily basis. In this context, the Frimesa Integrated Logistics Division seeks to structure its recruitment and selection procedure, with the aim of defining the desired profile for vacancies in terms of skills and competencies. This aims to enable a more accurate assessment during selection, making it easier to hire candidates who are more aligned with the desired profile for the position. The present study structured an instrument, using a multicriteria model, to assist in defning the vacancy profile, as well as to support the candidate selection decision. The work is characterized as a case study, adopting a qualitativequantitative approach in exploratory and descriptive research, using primary and secondary data. In the literature review, the Bibliographic Portfolio was used through the Knowledge Development Process – Constructivist (Proknow-C) instrument, with the quantification and analysis of the selected articles to provide a more in-depth understanding of the topic of multicriteria analysis in candidate selection and find the most relevant jobs. The construction of the instrument followed the multi-criteria analysis methodology to support constructivist decisions, comprising the structuring, evaluation and recommendation phases. The results obtained included the identification of three major areas of concern for the decision maker, with the formulation of 57 criteria for evaluating candidates in the recruitment and selection process in terms of skills and competencies, ordinal and cardinal measurement for each criterion with their reference levels, and integration through replacement fees. Furthermore, a simulation was carried out using the instrument developed to evaluate the candidates' performance, presenting the results through ranking and radar graph. Finally, an action plan was presented with proposals to improve the recruitment and selection process in the logistics area, concluding in this study that the methodology effectively played its role in defining the vacancy profile, facilitating the understanding of the desired skills and competencies and, thus, supporting the vacancy manager's decision in choosing the candidate with the closest profile and appropriate to the specific context of the study.